Design Cost Control in Risk Management with the Expected Money Value (Emv) and Hirarc Method at Pt Xyz Jawa Timur Surabaya - Rahardi Wardhana; Lukmandono (Universitas Muhammadiyah Sidoarjo, 2020)
This Operation of production area A6 workshop in PT XYZ can protecally lead to risk of accidents due to contact between worker with machines that operate like geka machine. The accidents caused by companies not yet know how the potentially dangerous and risks of working in the garage area lathe, as well as the lack of good implementation of procedures before entering the work area. From the accident required a determinan of hazard and risk analysis on production A6 workshop conducted by using HIRARC (Hazard Identification and Risk Assessment Control) and conduct a risk assessment to provide an assessment of the result of multiplication Severity and Likelihood that refers to the Department of Ocupational Safety and Health Ministry Guidlines of Human Resources Malaysia